2018
DOI: 10.1111/zsc.12328
|View full text |Cite
|
Sign up to set email alerts
|

Leopard tortoises in southern Africa have greater genetic diversity in the north than in the south (Testudinidae)

Abstract: In contrast to mammals, little is known about the phylogeographic structuring of widely distributed African reptile species. With the present study, we contribute data for the leopard tortoise (Stigmochelys pardalis). It ranges from the Horn of Africa southward to South Africa and westwards to southern Angola. However, its natural occurrence is disputed for some southern regions. To clarify the situation, we used mtDNA sequences and 14 microsatellite loci from 204 individuals mainly from southern Africa. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Fritz et al (2010) revealed that mtDNA sequences that were previously identified with the distinct subspecies S. p. babcocki represent nuclear mitochondrial insertions (numts), whereas they found no evidence for the validity of this subspecies and recommended to synonymize it into the nominotypical subspecies. Building on these results, two later studies (Spitzweg et al 2019;Dajčman et al 2021) focused on the southern part of the distribution of S. pardalis. Using mtDNA sequences (1,136 bp) and 14 microsatellite loci, Spitzweg et al (2019) identified two major genetic clusters: A southern cluster from southern coastal South Africa and a northern cluster, distributed from Namibia across northern South Africa to adjacent Mozambique.…”
Section: Phylogeographymentioning
confidence: 94%
See 2 more Smart Citations
“…Fritz et al (2010) revealed that mtDNA sequences that were previously identified with the distinct subspecies S. p. babcocki represent nuclear mitochondrial insertions (numts), whereas they found no evidence for the validity of this subspecies and recommended to synonymize it into the nominotypical subspecies. Building on these results, two later studies (Spitzweg et al 2019;Dajčman et al 2021) focused on the southern part of the distribution of S. pardalis. Using mtDNA sequences (1,136 bp) and 14 microsatellite loci, Spitzweg et al (2019) identified two major genetic clusters: A southern cluster from southern coastal South Africa and a northern cluster, distributed from Namibia across northern South Africa to adjacent Mozambique.…”
Section: Phylogeographymentioning
confidence: 94%
“…Building on these results, two later studies (Spitzweg et al 2019;Dajčman et al 2021) focused on the southern part of the distribution of S. pardalis. Using mtDNA sequences (1,136 bp) and 14 microsatellite loci, Spitzweg et al (2019) identified two major genetic clusters: A southern cluster from southern coastal South Africa and a northern cluster, distributed from Namibia across northern South Africa to adjacent Mozambique. Microsatellite data indicated further substructure and greater genetic diversity within the northern cluster.…”
Section: Phylogeographymentioning
confidence: 94%
See 1 more Smart Citation